1994
DOI: 10.1002/pro.5560030105
|View full text |Cite
|
Sign up to set email alerts
|

Structural analysis and localization of the carbohydrate moieties of a soluble human interferonγreceptor produced in baculovirus‐infected insect cells

Abstract: A soluble form of the human interferon y receptor that is required for the identification of interferon y antagonists was expressed in baculovirus-infected insect cells. The protein carried N-linked carbohydrate and showed a heterogeneity on denaturing polyacrylamide gels. We investigated the utilization of the potential sites for N-linked glycosylation and the structure of the carbohydrate moieties of this soluble receptor. Amino acid sequence analysis and ion spray mass spectrometry revealed that of the five… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 39 publications
2
17
0
Order By: Relevance
“…In contrast, our data indicates clearly that CMP-NeuAc is not available in the insect cells we studied for the synthesis of sialylated N-glycans. This result concurs with several studies that report the inability of Spodoptera-(Sf 9), Estigmena-, and Trichoplusia-derived cell lines to perform this modification Kulakosky et al, 1998;Manneberg et al, 1994;Ogonah et al, 1996). However, Mamestra brassicae and Manduca sexta cells have been reported as being capable of sialylating the N-glycans of recombinant human plasminogen (Davidson and Castellino, 1991b).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In contrast, our data indicates clearly that CMP-NeuAc is not available in the insect cells we studied for the synthesis of sialylated N-glycans. This result concurs with several studies that report the inability of Spodoptera-(Sf 9), Estigmena-, and Trichoplusia-derived cell lines to perform this modification Kulakosky et al, 1998;Manneberg et al, 1994;Ogonah et al, 1996). However, Mamestra brassicae and Manduca sexta cells have been reported as being capable of sialylating the N-glycans of recombinant human plasminogen (Davidson and Castellino, 1991b).…”
Section: Discussionsupporting
confidence: 94%
“…Numerous studies have shown that baculovirusinfected insect cells differ markedly from mammalian cells in this respect. The latter are generally capable of complex type N-glycan processing whereas insect cells, such as those derived from the lepidopteran insect Spodoptera frugiperda (Sf 9), produce proteins with truncated glycans, notably trimannosyl core structures [Man (3)GlcNAc (2)] plus or minus fucose Klenk, 1996;Kretzschmar et al, 1994;Manneberg et al, 1994). However, the ability of insect cells to perform complex N-glycosylation may be dependent on the stage of the baculovirus-infection cycle (Davidson and Castellino, 1991a), the timing of expression (Jarvis and Finn, 1996), or the insect-cell type (Davidson and Castellino, 1991b;Davis and Wood, 1995;.…”
Section: Introductionmentioning
confidence: 99%
“…1a). Previous characterization of insect-cell glycosylation has shown the most common N-linked glycan to be a hexasaccharide of 1039 Da (Manneberg et al, 1994). The predicted molecular weight of sIL-10R1 is 24 392 Da.…”
Section: Resultsmentioning
confidence: 98%
“…units and one GlcNac 2 Man 3 unit, assuming that all three sites are occupied Rasmussen et al, 1996;Karlsen et al, 1998!. The predominant species of N-linked glycans observed from insect cell expression have so far been hexasaccharides with and without a fucose subunit linked to the proximal N-acetyl glucosamine residue~Graben-horst et al, 1993;Manneberg et al, 1994!. Glycosylated HBP purified from human blood or produced by insect cells~native recombinant HBP!…”
mentioning
confidence: 99%
“…Abbreviations: CLP, cecal ligation and puncture; Fuc, fucose; GlcNac, N-acetylglycosamine; HBP, heparin binding protein; HEPES, N-~2-hydroxyethyl!piperazine-N9-2-ethanesulfonic acid; LPS, lipopolysaccharide; Man, mannose; ng-HBP, nonglycosylated HBP; PCR, polymerase chain reaction; PDB, Protein Data Bank; PKC, protein kinase C; RMSD, root-meansquare deviation; SDS-PAGE, sodium dodecyl sulfate-polyacrylamide gel electrophoresis. species of N-linked glycans observed from insect cell expression have so far been hexasaccharides with and without a fucose subunit linked to the proximal N-acetyl glucosamine residue~Grabenhorst et al, 1993;Manneberg et al, 1994!. Glycosylated HBP purified from human blood or produced by insect cells~native recombinant HBP! has in recent years been used to clarify the biological functions of HBP.…”
mentioning
confidence: 99%